Contiki IEEE 802.15.4 MAC layer protocols: implementation and evaluation of node’s throughput and power consumption - Abdulkarem, Mohammed; Samsudin, Khairulmizam; A. Rasid, Mohd Fadlee; Rokhani, Fakhrul Zaman (Springer, 2022)
In wireless sensor networks, providing flexibility in the selection of Medium Access Control (MAC) protocols to be implemented in an operating system (OS) becomes critical to best meet the requirements of each certain application. Since OS architecture and network stack protocol overhead have an effect on a node’s ability to transmit data, analytical studies often fail to foretell the achievable throughput from an application’s perspective. In Contiki OS, there are constraints at the specific level of the network stack and due to implementation of the provided MAC layer protocol, IEEE 802.15.4 unslotted CSMA/CA, which limit node’s throughput and the available bandwidth in IEEE 802.15.4-based networks and as a result impact node’s power consumption. In this paper, a TDMA-based MAC scheme, namely, lightweight time division multiple access (L-TDMA), is developed and implemented on Contiki to achieve high throughput and low power consumption by overcoming the existing constraints on the networking stack’s implementation of MAC layer on Contiki. The L-TDMA MAC scheme’s performance is evaluated using simulation and experimental testbed to determine its effectiveness and efficiency in comparison to different versions of IEEE 802.15.4 CSMA/CA-based protocols. The results demonstrate that L-TDMA scheme can significantly enhance node’s throughput, average channel throughput, power efficiency, and prolong battery lifespan.